2015
DOI: 10.1159/000439550
|View full text |Cite
|
Sign up to set email alerts
|

<smlcap>L</smlcap>-Carnitine Ameliorates Cancer Cachexia in Mice Partly via the Carnitine Palmitoyltransferase-Associated PPAR-&#947; Signaling Pathway

Abstract: Background:L-Carnitine has been demonstrated to ameliorate cachectic symptoms. In the present study, we sought to investigate the role of the peroxisome proliferator-activated receptor-γ (PPAR-γ) signaling pathway in the ameliorative effects of L-carnitine on cancer cachexia in a colon-26 tumor-bearing mouse model. Methods: The cachectic mice received L-carnitine (p.o.) or etomoxir (i.p.), or pioglitazone hydrochloride (p.o.) or GW9662 (i.p.). The physiologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…1e). The selected ALCAR concentrations are in line with our previously results on endothelial cells, and other preclinical and clinical studies [17, 20, 24, 30, 36]. The effect of ALCAR on cell growth was in part due to induction of apoptosis, as determined by flow cytometry.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…1e). The selected ALCAR concentrations are in line with our previously results on endothelial cells, and other preclinical and clinical studies [17, 20, 24, 30, 36]. The effect of ALCAR on cell growth was in part due to induction of apoptosis, as determined by flow cytometry.…”
Section: Resultssupporting
confidence: 82%
“…Carnitine has been reported as highly efficient in the downregulation of pro-inflammatory cytokines TNF-α and IL-6 in murine models of cancer cachexia [24, 36], liver fibrosis [23] and in blocking TNF-α-induced insulin resistance in skeletal muscle cells [48].…”
Section: Discussionmentioning
confidence: 99%
“…PPARb/d is the least well-characterized of the PPARs, but it is ubiquitously expressed in most tissues, regulates blood cholesterol and glucose levels, and is involved in fatty acid oxidation (43). Because PPARs play an obvious role in regulating whole body energy homeostasis, there has been significant success in modulating these transcription factors for the benefit of patients with diabetes, dyslipidemia, and atherosclerosis (44); and promising anticatabolic efficacy has been observed with PPAR agonists in mouse models of Lewis lung carcinoma (45), colon adenocarcinoma (46), and non-small-cell lung cancer (47). PPARg is 1 of the main regulators of adipocyte differentiation (48,49) and is downregulated in SkM of patients with breast cancer (23) and BC-PDOX-bearing mice.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, multiple lines of research have suggested that a combination treatment of butyrate and carnitine/acetylcarnitine can exert greater effects on cancerous cells than butyrate treatment alone, possibly by enhancing butyrate localization to the mitochondria [ 99 , 100 ]. Oral l -carnitine supplementation also mitigated cancer cachexia symptoms in BALB/c mice injected with adenocarcinoma cells [ 101 , 102 ].…”
Section: Butyrate In the Gastrointestinal Tractmentioning
confidence: 99%